Captive and Captor Representations at Canadian Penal History Museums - Chen, Ashley; Fiander, Sarah; Piché, Justin; Walby, Kevin (Qualitative Sociology Review, 2016)
This article examines representations of prisoners and prison staff from 45 penal tourism sites across Canada. Drawing from literature on representations of criminal justice, we demonstrate that the objects, signs, and symbolism in these heritage sites are curated in ways that can create separation between penal spectators and prisoners. Positive representations of prison staff stand in contrast to depictions of prisoners who are often demonized in museum displays through emphasis placed on narratives, relics, and images of danger and violence. Arguing that these depictions generate conditions for the support and justification of punitive practices including incarceration, we conclude by reflecting on what our findings add to social science literature on representations of captives and captors.